RUMEN pH AND MICROBIAL POPULATION OF YANKASA RAMS FED ENSILED SUGARCANE WASTE FORTIFIED WITH POULTRY LITTER - Ashiru, R. M.; Sariyyu, Sayuku; Abdulhamid, S. U.; Galadima, N. M.; Abubakar, M.; Abubakar, M. M.; Wudil, A. A.; Abdullahi, R.; Ado, F. H. (FUDMA Journal of Sciences, 2024)
Rumen contents may be observed for physical aspects (color, odor, consistency, sedimentation) and the chemical characteristics (pH, glucose, fermentation, nitrate reduction and methylene blue reduction test) and biological parameters (bacteria, protozoa and fungi) (Donato et al., 1999). The study was conducted to evaluate the effects of feeding ensiled sugarcane waste (ESCW) fortified with poultry litter (PL) to Yankasa rams on rumen fluid characteristics using 16 rams (mean initial BW 28.94 ± 5.77 kg; aged 12 to 18 months). Sugarcane waste was mixed with poultry litter in 3:1 and ensiled for 21 days, then use compound a complete diet. The rams were allocated to four groups on the basis of body weights into control group without ESCW (CG) as treatment groups (T1), 15% (T2), 30% (T3) and 45% (T4) in a Completely Randomized Design (CRD) and fed ad libtum for 84 days. At the end of the experiment, ten (10) ml of rumen fluid was drawn from individual experimental animal before feeding at 0 hr and 3 hrs and 6 hrs after meal. Parameters observed were pH, rumen bacteria and fungi biomass. The results showed that rumen bacteria and fungi counts were significantly (P
Keywords: Fungi; Microbes; pH; Sample; Bacteria